Meningkatkan Pemahaman Warga Desa Cigendel, Kecamatan Pamulihan Tentang Perbankan Syariah Melalui Kegiatan Sosialisasi - Hamid, Abdul; S, Sutopo; Purwanti, Neli (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Sharia banking is a banking system based on Sharia or Islamic law. A Sharia bank is a bank that operates based on Sharia principles. The problem in Waitu Jaya village is that the public lacks understanding and knowledge about Sharia banking transactions, so many people engage in loan sharking and some still use illegal banks. The purpose of socialization activities is to increase the public's knowledge and understanding of sharia banking, reduce the use of illegal banks, and reduce usury practices. The implementation of this activity is to approach the community and conduct outreach on Shariah Banking using PowerPoint and whiteboards in order to provide knowledge and understanding about Shariah Banking to the public. Based on the results of their philanthropic activities, they begin to understand and understand Sharia banking operations and become interested in trying to save in Sharia banks by reducing the use of illegal banks and Ribawi practices.